Case Report: Treatment of a Comorbid Attention Deficit Hyperactivity Disorder and Obsessive–Compulsive Disorder With Psychostimulants - Dogan-Sander, Ezgi; Strauß, Maria (Frontiers in Psychiatry, 2021)
Introduction Attention deficit hyperactivity disorder (ADHD) is a common disease in childhood and adolescence. In about 60% of pediatric patients, the symptoms persist into adulthood. Treatment guidelines for adult ADHD patients suggest multimodal therapy consisting of psychostimulants and psychotherapy. Many adult ADHD patients also suffer from psychiatric comorbidities, amongst others obsessive-compulsive disorder (OCD). The treatment of the comorbidity of ADHD and OCD remains challenging, as the literature is sparse. Moreover, the impact of psychostimulants on obsessive-compulsive symptoms is still unclear. Case Presentation Here, we report on a 33-year-old patient with an OCD who was unable to achieve sufficient remission under long-term guideline-based treatment for OCD. The re-examination of the psychological symptoms revealed the presence of adult ADHD as a comorbid disorder. The patient has already been treated with paroxetine and quetiapine for the OCD. Due to the newly established diagnosis of ADHD, extended-release methylphenidate (ER MPH) was administered in addition to a serotonin reuptake inhibitor. After a dose of 30 mg ER MPH, the patient reported an improvement in both, the ADHD and the obsessive-compulsive symptoms. After discharge, the patient reduced ER MPH without consultation with a physician due to subjectively described side effects. The discontinuation of medication led to a renewed increase in ADHD and obsessive-compulsive symptoms. The readjustment to ER MPH in combination with sertraline and quetiapine thereafter led to a significant improvement in the compulsive symptoms again. Conclusion The present case shows that in ADHD and comorbid obsessive-compulsive disorder, treatment with psychostimulants can improve the obsessive-compulsive symptoms in addition to the ADHD-specific symptoms. To our knowledge, this is only the second case report describing a treatment with ER MPH for an adult patient with OCD and ADHD comorbidity in the literature. Further research, especially randomized controlled trials, are needed to standardize treatment options.